Understanding post-Crisis price deviations in Europe: disintegration or mere adjustment? - Glushenkova, Marina; Zachariadis, Marios (Springer, 2018)
The paper investigates the process of European integration using law of one price (LOP) deviations for a large number of individual goods and services during the recent Crisis. We find that the degree of integration of Eurozone economies continued to increase during this period. Importantly, we trace the location of individual goods in the distribution of LOP deviations so as to understand how price advantage or disadvantage has evolved or persisted during the Crisis. We find that rigidities rendering prices in some markets higher persisted during the same period. Thus, while well-deserved policy emphasis has been placed by the Eurozone on correcting fiscal imbalances and on monetary policy to address the resulting deflationary bias, our work suggests that little has been done in practice to break structural rigidities in goods and services markets during the period under study. Finally, comparing the distributions of LOP deviations for each of the Eurozone economies, we show that to the extent that there was adjustment for some of these economies this did not occur via the same channels for all Eurozone countries, suggesting different non-tradeables and tradeables adjustment mechanisms being in place in different countries.